(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study investigates the character of Prince Hamlet in William Shakespeare’s renowned tragedy Hamlet, focusing on his portrayal as a tragic hero through the lens of internal conflict and moral dilemma. The article employs an interdisciplinary approach, combining Aristotelian definitions of tragedy with modern psychological and philosophical frameworks to analyze Hamlet’s character development. By examining soliloquies, key dialogues, and turning points in the play, the paper highlights how Hamlet’s introspection, ethical reasoning, and existential inquiries contribute to his downfall. It concludes that Hamlet’s tragedy lies in his inability to reconcile thought with action in a morally ambiguous world